2018
DOI: 10.1038/s41598-018-24293-3
|View full text |Cite
|
Sign up to set email alerts
|

Human mandibular shape is associated with masticatory muscle force

Abstract: Understanding how and to what extent forces applied to the mandible by the masticatory muscles influence its form, is of considerable importance from clinical, anthropological and evolutionary perspectives. This study investigates these questions. Head CT scans of 382 adults were utilized to measure masseter and temporalis muscle cross-sectional areas (CSA) as a surrogate for muscle force, and 17 mandibular anthropometric measurements. Sixty-two mandibles of young individuals (20–40 years) whose scans were wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 51 publications
4
69
0
1
Order By: Relevance
“…the shape of class II mandibles is dependent of their small size and the shape of class II mandibles, of their large size. Same as genetics, masticatory muscle force has shown to have an effect on mandibular shape in modern individuals [15]. But large shape variation leading to the extreme features shown by individuals with malocclusions could be linked to the effect of other factors, such as nutrition and basal metabolism in modern humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the shape of class II mandibles is dependent of their small size and the shape of class II mandibles, of their large size. Same as genetics, masticatory muscle force has shown to have an effect on mandibular shape in modern individuals [15]. But large shape variation leading to the extreme features shown by individuals with malocclusions could be linked to the effect of other factors, such as nutrition and basal metabolism in modern humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inducing masseter muscle paralysis in adult mice leads to an increased activity of the bone resorption marker RANKL, followed by a reduction of bone tissue per area and trabecular thickness of the condyle head [13]. Using medical data from modern populations, it has been observed that muscle force is only weakly related to cranial shape [14], but more so to the shape of the mandible [15].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the dietary change, children's mandibles rotated anteriorly, facilitated by increased gonial angle and stronger chewing muscles (Ingervall and Bitsanis 1987). These changes have also been observed in more recent studies of mandibular metrics and masticatory muscles (Sella-Tunis et al 2018). Based on the studies outlined above, dietary consistency has a clear impact on masticatory stimulation, specifically in relation to gonial angle and facial form.…”
Section: The Epidemiological Occlusal Transitionmentioning
confidence: 72%
“…Permanent dentition is almost fully erupted by late adolescence, with the variable exception of third molars. The jaw has developed into what will most likely be its adult form, with no significant morphological or metric changes likely to occur until senescence (Scheuer and Black 2004). The idea of functional integration can be used to explain this.…”
Section: The Epidemiological Occlusal Transitionmentioning
confidence: 99%
See 1 more Smart Citation